Peran dan Tantangan Guru di Era Artificial Intelligence - Muhammad Badrus Sholeh; Himmatul Aliyah; Aprilia Tri Ratna Nugrahenni (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2023)
Artificial Intelligence (AI) has the potential to transform the way we teach and learn. In recent years, there has been a growing interest in the application of AI in education, with a range of initiatives and products emerging in the market. This review article provides an overview of the literature focusing on the following areas: the role of Artificial Intelligence in teacher education, the roles of teachers in the Artificial Intelligence era, teacher’s role predicament in the era of Artificial Intelligence, teacher’s role orientation in the era of Artificial Intelligence, challenges of teachers in the era of Artificial Intelligence, and the ways of facing the teachers’ challenges in the era of Artificial Intelligence.